Characteristics of Farmers in Suboptimal Land Agroecosystems and the Implications of the Application of Farm Technology - Suharyon Suharyon; Busyra B Saidi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
The area of West Tanjung Jabung District is dominated by tidal land agroecosystems so that the farming pattern that develops is based on tidal land. This research aimed to study the characteristics of farmers in tidal land agroecosystems and their implications for the application of farming technology. The research was conducted in Bunga Tanjung Village, Betara Subdistrict, West Tanjung Jabung District in 2019, involving 40 farmers who were randomly selected as respondents. The descriptive data analysis showed the first, farming on tidal land was characterized by the control of relatively unprocessed and cultivated farm land, low crop intensity of food commodities, and low levels of productivity resulting in unfulfillable farming results properly. The second, the biophysical conditions of farming land wereless conducive to influence the decisions of farmers to Apply farming technology. The third, the opportunity to increase farming productivity in tidal lands was still wide open by optimizing the potential utilization of farmland resources based on the strengths and weaknesses of farmers. The fourth, the strategies to increase productivity in tidal land agroecosystem areas were conducted by diversifying into multi- enterprises, implementing integration patterns between commodities, accelerating technology dissemination, and encouraging the growth of partnership networks. In order for these strategies to be implemented, it is necessary to have a soft credit scheme policy which in its implementation it is followed by assistance of extension agents and researchers.